Importance and control of geometric and kinematic accuracy in precision machining of parts in assembly operation aspect - Basara, Damian; Skoczylas, Leszek (Technologia i Automatyzacja Montażu (Assembly Techniques and Technologies), 2020)
This paper presents general characteristics of methods for measuring kinematics and geometry of CNC machines. Implementation of the selected control methods at numerical centres is shown. The mentioned centres are a part of flexible production lines used for the production of parts in the aviation industry used to assembly power transmissions that require high-precision components. Adapted control methods allow automatic planned mode or forced mode to test the machine’s suitability for the machining process. The assessment applies to geometry and kinematics of the CNC machine. This is an Open Access article distributed under the terms of the Creative Commons Attribution License CC BY 4.0 (https://creativecommons.org/licenses/by/4.0/)